Pengaruh Ukuran Perusahaan, Profitabilitas, Dan Reputasi Kantor Akuntan Publik Terhadap Intellectual Capital Disclosure - Radhiah Suri Utami; Henri Agustin (Jurnal Eksplorasi Akuntansi, 2020)
This research investigate the effect of Company Size, Profitability, and the Reputation of Public Accounting Firms on Intellectual Capital Disclosure in high-ic intensive companies listed on the Indonesia Stock Exchange in 2016-2018. The type of this research is descriptive and causality research. The research population are High-IC Intensive companies with a total 115 companies from bank, advertising, printing and media, and real estate sub sectors listed on the Indonesia Stock Exchange in 2016-2018, and the sample was determined using the purposive sampling method, with 82 sample from 115 High-IC Intensive companies. Multiple reggression was used to analysis the data. The result shows that company size have a negative and significant effect on intellectual capital disclosure. Profitability have a negative and not significant effect on intellectual capital disclosure. The reputation of the public accounting firm have a positive and significant effect on intellectual capital disclosure, but company size and profitability have failed to intellectual capital disclosure